Ubiquitous Computing Application and Wireless Sensor UCAWSN-14 - Park, James J. (Jong Hyuk); Pan, Yi; Chao, Han-Chieh; Yi, Gangman (Lecture Notes in Electrical Engineering,, 2015)
IT changes everyday's life, especially in education and medicine. The goal of ITME 2014 is to further explore the theoretical and practical issues of Ubiquitous Computing Application and Wireless Sensor Network. It also aims to foster new ideas and collaboration between researchers and practitioners. The organizing committee is soliciting unpublished papers for the main conference and its special tracks.